The fierce dispute for Memory, Truth and Justice in Guatemala - Figueroa Ibarra, Carlos (2025)
This paper argues that the fierce dispute over Memory, Truth and Justice that has been observed in recent years in Guatemala is nothing more than the continuation of the conflict that began in 1954. the advocates of oblivion, historical revisionism and impunity are the same ones who have defended the oligarchic order restored in 1954. Those who seek to preserve the memory of the atrocities, the historical clarification of human rights violations and the punishment of those responsible for the latter are followers of the who questioned the oligarchic restoration of 1954. This article also argues that the Guatemalan State has not had the will to absorb the demands made by the relatives of victims, survivors and human rights organizations. Either, the Guatemalan State has not had the will to turn the resolution of said demands into a source of legitimacy. For that reason, the victories of transitional justice do not legitimize the State but rather confirm the veracity of the violence that it carried out and question the legality and legitimacy of the order that it defended.